MINAT MEMBACA MAHASISWA PROGRAM STUDI PG-PAUD FKIP UNTAN PONTIANAK - Halida Halida (Jurnal Visi Ilmu Pendidikan, 2018)
Interest in reading is not something to be born just like that in a person, but something that belongs to someone for granted, but is something that can be developed. The general objective of this study was to determine the interest in reading students of PG-PAUD FKIP Untan. The results obtained from the research that is done on aspects of the feeling of pleasure with reading activities, students who receive a lower category, namely 11, 26%, being 33.52% and the category is quite high at 36, 54%. Higher category obtained a percentage of 18.68%. That means a low student interest in reading for pleasure with the feelings aspects of the activity of reading. For the aspects of awareness of the importance of reading, students who receive lower categories, namely 9.07%, 12.64%, and the category was quite high at 36.95%. For high category obtained percentage of 41.35%. Judging from the above data, the percentage of these were included in the analysis. Aspects aspects of attention to the activities of students obtained reading books that fall within the low at 7.56%, currently 27.05%, and the category is quite high at 50.13%. Judging from the percentages then being included in the analysis. It can be concluded that the interests of students Prodi PG-PAUD FKIP Untan still low. It is strongly advised Prodi PG-PAUD students in general and students of PG-PAUD force in 2013 specifically to continue to increase interest in reading by way penchant frequently visit the campus library and local libraries to read anything what.